2009
DOI: 10.1016/j.bpj.2008.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Apolipoprotein A-I in High-Density Lipoproteins by Molecular Dynamics

Abstract: Apolipoprotein (apo) A-I is an unusually flexible protein whose lipid-associated structure is poorly understood. Thermal denaturation, which is used to measure the global helix stability of high-density lipoprotein (HDL)-associated apoA-I, provides no information about local helix stability. Here we report the use of temperature jump molecular dynamics (MD) simulations to scan the per-residue helix stability of apoA-I in phospholipid-rich HDL. When three 20 ns MD simulations were performed at 500 K on each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 58 publications
(90 reference statements)
6
62
0
Order By: Relevance
“…With the exception of R188, all other fi ve residues involved in salt bridges are conserved in mammals. Consistently with these observations, temperature jump molecular dynamic simulation ( 30,31 ) indicated that the E89-R177 and E111-H155 are more stable than the E78-R188 salt bridge. Thus it is possible that elimination of the negatively charged residues D89 and E111 and, to a lesser extent, E78, may destabilize the intermolecular interactions of the apoA-I dimer or the hairpin bound to HDL and may predispose to dyslipidemia.…”
Section: Binding Of Apoa-i Forms To Triglyceride-rich Emulsionssupporting
confidence: 60%
“…With the exception of R188, all other fi ve residues involved in salt bridges are conserved in mammals. Consistently with these observations, temperature jump molecular dynamic simulation ( 30,31 ) indicated that the E89-R177 and E111-H155 are more stable than the E78-R188 salt bridge. Thus it is possible that elimination of the negatively charged residues D89 and E111 and, to a lesser extent, E78, may destabilize the intermolecular interactions of the apoA-I dimer or the hairpin bound to HDL and may predispose to dyslipidemia.…”
Section: Binding Of Apoa-i Forms To Triglyceride-rich Emulsionssupporting
confidence: 60%
“…A second weakness in the SANS data is that the ratio of 200 POPC to 2 apoA-I used does not form stable dimeric (R2) apoA-I particles (12,40). Because SANS data collection takes many hours, particle fusion may have occurred during this long time in the neutron beam, thus confusing the curve fitting.…”
Section: Discussionmentioning
confidence: 99%
“…Further details about CG parameters can also be found in our previous work ( 18 ). The protein secondary structure was assigned using as a reference the one generated by AA simulations ( 13 ). This approach was employed to give more fl exibility to the apoA-I chains ( 12,18 ) of the previously described CG simulations for particles of identical molar ratios.…”
Section: Cg Force Fi Eldmentioning
confidence: 99%
“…Cross-linking data by Silva et al ( 34 ) suggests the simulations of dHDL and sHDL ( 12 ). More recently, we developed methodology termed particle shrinkage that allows simulation of dHDL containing full-length apoA-I (12)(13)(14)(15).…”
Section: Cg MD Simulationsmentioning
confidence: 99%